How do antimicrobial peptides destroy membranes? A Molecular Dynamics perspective - Park, Peter (2023)
Cationic alpha-helical antimicrobial peptides (CHAMP) are potential candidates as novel drugs against resistant bacteria. CHAMPs are short amphipathic, membrane-active peptides in many organisms as part of their innate immune defense system. CHAMPs spark interest in pharmaceutical applications due to their ability to bear less risk of inducing bacterial resistance than conventional antibiotics, selectivity towards bacteria and fungi, and fast antimicrobial action. Their detailed mechanism of action on membranes needs to be clarified. Elucidating CHAMPs\' mode of action can provide relevant information that can be used to better design new CHAMPs with higher efficacy and selectivity. Here, we used Molecular Dynamics (MD) simulations to investigate the detailed mode of action of BP100 (H-KKLFKKILKYL-NH2), a promising CHAMP, on membranes. We characterized the initial interaction between a single BP100 and membranes using atomistic simulations. We described peptide flip, a dynamic phenomenon in which BP100 binds to the membranes, rotates and penetrates the membrane core, and causes local membrane effects, such as thinning, negative curvature, and a decrease in lipid lateral diffusion. We show peptide flip is a common step in the CHAMP/membrane interaction, using other similar CHAMPs: Decoralin, Neurokinin-1, and Temporin-L. Using coarse-grained MD, we studied the CHAMPs peptide concentration effect on vesicles, showing CHAMP-induced membrane budding at highly curved regions of negatively charged vesicles at a high peptide:lipid ratios. Our results suggest that the carpet mode of action fits the description of CHAMPs lysis activity, and we discuss the importance of significant hydrophobic residues in CHAMPs design and activity